Reservation system for premier lounge / Muhammad Faizal Samat ...[et al.] - Samat, Muhammad Faizal; Mohamad Razali, Mohamad Safwan; Saiful Muluk, Nur Mazidah; Nizam, Muhamad Farhan; Nazori, Nurul Najwa Zahira (2020)
Technology is the application of scientific knowledge for practical purposes, especially in industry.Technology is also used to make things easier in our daily life. For the reservation systems we are focusing more in the reservation of the premier lounge that is located in the UiTM Cawangan Kelantan. This is because in order to use the premier lounge, they have to write on the whiteboard and that become a problems because it can be easily erased and have no security over the reservation. The objective of the reservation system is to make the reservation in using the premier lounge become easier in the university. This reservation system also save time and increase the security in making the reservation. This system can help the user to know the availabilty of the premier lounge and help to reduce and avoid redundancy in making the reservation of the premier lounge.The reservation systems were invented to help the user in the process of the reservation of the premier lounge in order to make the its easier to do work in that premier lounge. The reservation will be more secure and will be easier because itspeed the time to reserve the room. This system can be used in the university which can help to increase the effiiciency of the management in the universit